Strong brands : how brand strategy and brand communication contribute to build brand equity : the case of navigator - Baeva, Daniela Yasenova (2011)
Dissertação de mestrado em Marketing, apresentada à Faculdade de Economia da Universidade de Coimbra, sob a orientação de Arnaldo Matos Coelho.